Enhancing Maritime Vocational Training in Naval Engine Operations: A Study in North Sulawesi - Iksan Saifudin; Palapa , Arika; Sutopo , Fajar; Teriyanti, Teriyanti; Alamsyah, Jaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Background: In North Sulawesi, maritime vocational schools are central to producing skilled cadets for Indonesia’s shipping and port industries. However, a persistent gap exists between institutional training and the technical realities of naval engine operations onboard vessels, leading to underprepared graduates. Original Value of the Analysis: This study provides a regionally grounded contribution by integrating the perspectives of maritime professionals and educators in North Sulawesi. Unlike prior studies with broader or policy-level focus, this research highlights localized insights into improving training effectiveness through industry-based knowledge. Objectives: The research aimed to explore how the integration of veteran seafarers’ operational expertise and vocational lecturers’ instructional experience can enhance curriculum relevance, student competency, and practical learning outcomes in naval engine education. Methodology: Employing a descriptive qualitative approach, the study collected data through in-depth interviews and thematic analysis involving two retired maritime professionals and ten vocational lecturers, all with substantial sea-going and teaching experience. Results: Findings demonstrated strong agreement on the need for curriculum reform, increased hands-on practice, mentorship programs, and competency-based assessment aligned with engine room demands. The combination of professional and pedagogical insight proved critical in identifying reform strategies. Conclusions: This research offers a locally relevant framework for strengthening maritime vocational training in North Sulawesi, supporting policy and institutional changes toward industry-aligned, sustainable maritime education.